Oral pyogenic granuloma: one reactive hyperplastic lesion of the gingiva - Narendra, Suryakanta; Bose, Chaitali; Rout, Niranjan (International Journal of Research in Medical Sciences, 2017)
The term pyogenic granuloma refers to a disorder of the skin, oral mucosa and the gingiva, that usually presents as a solitary polypoid capillary hemangioma like growth often resulting from local irritation and trauma. It is manifested as an inflammatory response with similar characteristics to those of a granuloma. Different terminologies are used for this lesion by different investigators like, benign vascular tumor of pregnancy, granuloma pediculatum benignum, granuloma pyogenicum, Crocker and hartzell's disease. This lesion even if looks like a tumor, is non neoplastic in nature and present itself in various clinical and histological forms. Lack of association of pyogenic etiopathogenesis does not justify the use of terminology of pyogenic granuloma. In this article we are presenting a case series of pyogenic granuloma in different locations giving an insight into their myriad of etiologies and presenting the review of literature for its inclusion as one classified hyperplastic lesion of oral cavity.